Problems and Solutions in the Professional Development of Rural Primary School Teachers in Zhoukou-China - Wang, Wenna; Anwar, Khoirul (International Conference on Law, Technology, Spirituality and Society (ICOLESS); Vol 4 (2024): The 7th International Conference on Law, Technology, Spirituality and Society (ICOLESS), 2024)
This study explores the teaching experiences of educators and identifies strategies that support the professional development of rural teachers in Zhoukou, China. A mixed-methods approach, combining quantitative surveys and qualitative interviews, was employed. Data were collected through 111 valid questionnaires distributed across six primary schools, and in-depth interviews were conducted with ten teachers selected for their diverse experiences and perspectives. The research highlights significant challenges faced by rural teachers, including high job pressure, limited training opportunities, inadequate compensation for external training, and insufficient professional development options. Despite these obstacles, teachers employ various strategies to enhance their skills, such as attending lectures, engaging in personalized learning, building learning communities, and adopting research-based classroom methodologies. However, these efforts are hindered by contextual, institutional, and personal limitations, as well as the lack of supportive professional environments. The findings emphasize the need for comprehensive measures to address these challenges and foster meaningful professional development for rural teachers in Zhoukou, China.